Alcoholics anonymous and twelve‐step recovery: A model based on social and cognitive neuroscience. (May 2014) - Galanter, Marc
<x xml:space="preserve">Abstract</x> Background In the course of achieving abstinence from alcohol, longstanding members of Alcoholics Anonymous (AA) typically experience a change in their addiction‐related attitudes and behaviors. These changes are reflective of physiologically grounded mechanisms which can be investigated within the disciplines of social and cognitive neuroscience. Objective This article is designed to examine recent findings associated with these disciplines that may shed light on the mechanisms underlying this change. Method Literature review and hypothesis development. Results Pertinent aspects of the neural impact of drugs of abuse are summarized. After this, research regarding specific brain sites, elucidated primarily by imaging techniques, is reviewed relative to the following: Mirroring and mentalizing are described in relation to experimentally modeled studies on empathy and mutuality, which may parallel the experiences of social interaction and influence on AA members. Integration and retrieval of memories acquired in a setting like AA are described, and are related to studies on storytelling, models of self‐schema development, and value formation. A model for ascription to a Higher Power is presented. Conclusion The phenomena associated with AA reflect greater complexity than the empirical studies on which this article is based, and certainly require further elucidation. Despite this substantial limitation in currently available findings, there is heuristic value in considering the relationship between the brain‐based and clinical phenomena described here. Scientific Significance There are opportunities for the study of neuroscientific correlates of Twelve‐Step‐based recovery, and these can potentially enhance our understanding of related clinical phenomena. (Am J Addict 2014;23:300–307)